Thermal, Visual, and Acoustic Comfort Assessment in Sustainable Elementary School Classrooms: A Case Study at SD Negeri 8 Ragunan, Jakarta - Panggabean, Siti Munawarah; Andandaningrum, Della; Susanti, Vitria (WISE Pendidikan Indonesia, 2025)
This research investigates the environmental comfort conditions—thermal, visual, and acoustic—in six functional spaces at SD Negeri 8 Ragunan, South Jakarta, a public elementary school recognized for its sustainability-focused infrastructure. The study emphasizes the relevance of indoor environmental quality in shaping students’ cognitive performance, well-being, and overall learning experience. A mixed-methods design was employed, combining quantitative field measurements with qualitative spatial analysis. Data collection included temperature (28.5°C–32.1°C), relative humidity (65%–78%), light intensity (263–712 lux), and sound levels (41.3–64.5 dBA), measured in four classrooms, one hall, and one teachers’ room. Qualitative data involved architectural observations on ventilation, daylight access, and environmental policy signage. Results were benchmarked against Indonesian national standards (SNI 6390:2011, SNI 6197:2020, SNI 6386:2000) and international guidelines (ASHRAE 55-2017, GBCI). Findings indicate that temperature and illumination were within permissible thresholds, and visual connectivity reached 94.83%, exceeding GBCI’s 75% standard. However, humidity levels consistently surpassed the 60% threshold, and noise levels occasionally exceeded recommended limits, particularly in rooms near traffic exposure. Moreover, anti-smoking signage was insufficient and inconsistently placed. These results highlight the need for integrated environmental management strategies in school buildings. The study contributes to the discourse on sustainable educational facilities and supports the implementation of SDG 4 (Quality Education) and SDG 11 (Sustainable Cities and Communities), particularly in rapidly urbanizing tropical regions.